Risks of Reproducing with a Genetic Disorder - Byler, Melissa Ciano; Lebel, Robert Roger (Seminars in Reproductive Medicine, 2013)
Male-factor infertility is the cause of reproductive issues in many couples. For approximately 15% of these men, the origin of the infertility is genetic. These causes include both chromosomal and single-gene disorders frequently impacting spermatogenesis. By identifying the genetic mechanism behind the infertility, we determine the ability of the couple to use assisted reproduction technologies. Use of these methods has ignited a new spectrum of concerns for the genetic competence of the offspring. By knowing what specific genetic risks exist for the offspring of men with these particular disorders, we are able to use preimplantation genetic diagnosis to detect these problems.
Keywords: male infertility; Klinefelter; XYY; AZF; androgen receptor; CFTR